Effects of the superior mesenteric artery approach versus the no-touch approach during pancreatoduodenectomy on the mobilization of circulating tumour cells and clusters in pancreatic cancer (CETUPANC): randomized clinical trial - Padillo Ruiz, Javier (2024)
Background: Patients with pancreatic ductal adenocarcinoma present early postoperative systemic metastases, despite complete oncological resection. The aim of this study was to assess two pancreatoduodenectomy approaches with regard to intraoperative circulating tumour cells and cluster mobilization and their potential association with the development of distant metastasis. Methods: Patients with periampullary tumours who underwent open pancreatoduodenectomy were randomly allocated to either the no-touch approach or the superior mesenteric artery approach. A total of four intraoperative portal vein samples (at the beginning of the intervention, after portal vein disconnection from the tumour, after tumour resection, and before abdominal closure) were collected to measure circulating tumour cells and cluster numbers. Primary outcomes were the intraoperative number of circulating tumour cells and cluster mobilization. Further, their potential impact on 3-year distant metastasis disease-free survival and overall survival was assessed. Results: A total of 101 patients with periampullary tumours were randomized (51 in the superior mesenteric artery group and 50 in the no-touch group) and 63 patients with pancreatic ductal adenocarcinoma (34 in the superior mesenteric artery group and 29 in the notouch group) were analysed. Circulating tumour cells and cluster mobilization were similar in both the no-touch group and the superior mesenteric artery group at all time points. There were no significant differences between surgical groups with regard to the median metastasis disease-free survival (12.4 (interquartile range 6.1–not reached) months in the superior mesenteric artery group and 18.1 (interquartile range 12.1–not reached) months in the no-touch group; P = 0.730). Patients with intraoperative cluster mobilization from the beginning to the end of surgery developed significantly more distant metastases within the first year after surgery (P = 0.023). Two intraoperative factors (the superior mesenteric artery approach (P = 0.025) and vein resection (P < 0.001)) were predictive factors for cluster mobilization. Conclusion: Patients undergoing pancreatoduodenectomy using either the no-touch approach or the superior mesenteric artery approach had similar circulating tumour cells and cluster mobilization and similar overall survival and metastasis disease-free survival. A high intraoperative cluster dissemination during pancreatoduodenectomy was a predictive factor for early metastases in patients with pancreatic ductal adenocarcinoma.